2023
DOI: 10.1038/s41467-023-38750-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fatty acid amide hydrolase as a metastasis suppressor in breast cancer

Isabel Tundidor,
Marta Seijo-Vila,
Sandra Blasco-Benito
et al.

Abstract: Clinical management of breast cancer (BC) metastasis remains an unmet need as it accounts for 90% of BC-associated mortality. Although the luminal subtype, which represents >70% of BC cases, is generally associated with a favorable outcome, it is susceptible to metastatic relapse as late as 15 years after treatment discontinuation. Seeking therapeutic approaches as well as screening tools to properly identify those patients with a higher risk of recurrence is therefore essential. Here, we report that the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The evidence gathered in this study reveals the profound importance of FAAH in the differentiation dynamics of MECs in the adult mammary gland, and raises potentially important implications for the pathogenesis of breast cancer. Recent work from our lab established that FAAH genetic inactivation in the MMTV-neu transgenic mouse model preceded the formation of highly proliferative, more aggressive tumors [ 27 ]. Here, we demonstrated that mammary glands from FAAH −/− mice show an expanded population of alveolar progenitors, which are the likely target for transformation in the MMTV-neu model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence gathered in this study reveals the profound importance of FAAH in the differentiation dynamics of MECs in the adult mammary gland, and raises potentially important implications for the pathogenesis of breast cancer. Recent work from our lab established that FAAH genetic inactivation in the MMTV-neu transgenic mouse model preceded the formation of highly proliferative, more aggressive tumors [ 27 ]. Here, we demonstrated that mammary glands from FAAH −/− mice show an expanded population of alveolar progenitors, which are the likely target for transformation in the MMTV-neu model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33,34] The biological roles of FAAH have been reported in the context of tumorigenicity of multiple cancers. [35,36] It has been demonstrated that FAAH was highly expressed in prostate cancer tissues and cell lines, and its knockdown was sufficient to inhibit the invasive ability of cancer cells. [37] Similarly, Ravi et al [38] reported that FAAH could enhance the tumorigenic and invasive effect in lung cancer by activating EGF/ EGFR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As well, it was stated that endogenous CB1 agonists as Anandamide, oleamide, and 2-Arachidonoylglycerol (works as CB1 and CB2 agonist) have an antiproliferative effect (Coelho et al 2023 ). Moreover, arvanil (which is a synthetic CB1 agonist) also inhibits cell proliferation (Tundidor et al 2023 ). Phytocannabinoids compounds were also tested in a study to investigate their abilities in inhibiting BC growth.…”
Section: Cannabis In Breast Cancermentioning
confidence: 99%